Media Pembelajaran Pengenalan Tumbuh-Tumbuhan Langka Berbahasa Inggris Berbasis Android Untuk Anak SD Menggunakan Unity 3D - Mutiara Putry; Ummul Khair; Munjiat Setiani Asih (Router : Jurnal Teknik Informatika dan Terapan, 2025)
The rapid advancement of technology in the field of education has provided numerous opportunities to enhance the learning experience. This study focuses on the development of an Android-based learning media for introducing rare plants, specifically designed for elementary school students. The application utilizes Unity 3D to create an engaging and interactive learning environment. By integrating English language learning with botany education, the application aims to enrich students' knowledge about rare plants while simultaneously improving their English language skills. This phase is followed by the design and development stages, where Unity 3D is used to create 3D models and interactive features. The application is designed to provide an interactive and enjoyable learning experience for elementary school students to explore rare plants. By using the Android platform and Unity 3D technology, the application allows students to discover various plant names in English. Results from a trial with 20 respondents on the Android-based learning media for introducing rare plants showed that 49.35% strongly agreed, 49.25% agreed, 1.37% were unsure, 0% disagreed, and 0% strongly disagreed.